Role of allergen-specific T-follicular helper cells in immunotherapy. Issue 6 (December 2018) - Yao, Yin; Wang, Zhi-Chao; Yu, Di; Liu, Zheng
Abstract : Purpose of review: The discovery of novel T-cell subsets including follicular helper T (Tfh) cells has broadened our knowledge on the complex immune networks in allergic diseases. This review summarizes the evidence for Tfh cells in controlling immune responses to allergens with a particular focus on immunoglobulin E (IgE) production and discusses the implication of such regulation in allergen-specific immunotherapy. Recent findings: Tfh cells support the production of IgE in animal models for allergic diseases. Among Tfh cells, the type 2 subset (Tfh2) is considered as the major player that secretes IL-4 and promotes the isotype switching to IgE. In human inflammatory airway diseases, including allergic rhinitis, asthma, and nasal polyps, the increased frequencies of circulating or tissue Tfh2 cells have been reported. Notably, the frequencies of Dermatophagoides pteronyssinus group 1 (Der p 1)-specific IL-4 + Tfh cells in blood positively correlated with serum Der p-specific IgE levels in allergic rhinitis patients. After allergen immunotherapy (AIT), Der p 1-specific IL-4 + Tfh cells declined in allergic rhinitis patients, which associated with the remission of clinical symptoms. Summary: Allergen-specific IL-4 + Tfh cells contribute to the production of allergen-specific IgE and correlate with clinical efficacy of AIT in allergic rhinitis patients, which suggest allergen-specific Tfh cells as a promising therapeutic target and biomarker for AIT in allergic rhinitis.